Exchange Rate Regime, Financial Market Bubbles and Long-Term Growth in China: Lessons from Japan - Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2016)
The paper argues that persistent current account surpluses and increasing foreign currency-denominated asset positions constitute long-term appreciation expectations on yuan and yen, which have made China and Japan vulnerable to U.S. interest rate cuts and appreciation expectation shocks. For both China and Japan – at different points of time – self-fulfilling runs into yuan and yen have triggered monetary policy expansions, which are identified as the breeding ground for overinvestment, speculative bubbles and post-bubble secular stagnation. To prevent a similar scenario for China capital controls, a tighter monetary policy and a fixed exchange rate regime are recommended.
Keywords: E32; E42; E58; 330; China; Japan; exchange rate policy; bubble economy; overinvestment; Hayek low interest rate policy; secular stagnation; capital controls; rebalancing